Dietary inflammatory index and telomere length in subjects with a high cardiovascular disease risk from the PREDIMED-NAVARRA study: cross-sectional and longitudinal analyses over 5 y - García-Calzón, Sonia; Zalba, Guillermo; Ruiz-Canela, Miguel; Shivappa, Nitin; Hébert, James R; Martínez, J Alfredo; Fitó, Montserrat; Gómez-Gracia, Enrique; Martínez-González, Miguel A; Marti, Amelia (The American journal of clinical nutrition, 2015)
Dietary factors can affect telomere length (TL), a biomarker of aging, through oxidation and inflammation-related mechanisms. A Dietary Inflammatory Index (DII) could help to understand the effect of the inflammatory potential of the diet on telomere shortening. This study aimed to determine the association of the DII with TL and to examine whether diet-associated inflammation could modify the telomere attrition rate after a 5-y follow-up of a Mediterranean dietary intervention. This was a prospective study of 520 participants at high cardiovascular disease risk (mean ± SD age: 67.0 ± 6.0 y, 45% males) from the PREDIMED-NAVARRA (PREvención con DIeta MEDiterránea-NAVARRA) trial. Leukocyte TL was measured by quantitative real-time polymerase chain reaction at baseline and after 5 y of follow-up. The DII was calculated from self-reported data by using a validated 137-item food-frequency questionnaire. Longer telomeres at baseline were found in participants who had a more anti-inflammatory diet (lowest DII score) (P-trend = 0.012). Longitudinal analyses further showed that a greater anti-inflammatory potential of the diet (i.e., a decrease in the DII) could significantly slow down the rate of telomere shortening. Moreover, the multivariable-adjusted OR for short telomeres (z score ≤20th percentile) was 1.80 (95% CI: 1.03, 3.17) in a comparison between the highest (proinflammatory) and the lowest (anti-inflammatory) DII tertiles. Similarly, a greater DII (greatest proinflammatory values) after a 5-y follow-up was associated with almost a 2-fold higher risk of accelerated telomere attrition compared with the highest decrease in DII (greatest anti-inflammatory values) during this period (P-trend = 0.025). This study showed both cross-sectional and longitudinal associations between the inflammatory potential of the diet and telomere shortening in subjects with a high cardiovascular disease risk. Our findings are consistent with, but do not show, a beneficial effect of adherence to an anti-inflammatory diet on aging and health by slowing down telomere shortening. These results suggest that diet might play a key role as a determinant of TL through proinflammatory or anti-inflammatory mechanisms. This trial was registered at controlled-trials.com as ISRCTN35739639.